Penelitian dan Pengembangan Smart Patient Bed dengan Sistem Pemantauan Berat Badan Pasien Berbasis IoT - Arianto, Eko (Universitas Putra Indonesia YPTK Padang, 2024)
Patient beds are crucial medical equipment in healthcare facilities, and this study aims to enhance the functionality of conventional patient beds by transforming them into electric beds equipped with a patient weight monitoring system. Against the backdrop of a shortage of beds meeting standards, this development is anticipated to improve patient care efficiency and fulfill healthcare standards. The research methodology involves analyzing the crank drive system of patient beds, replacing manual cranks with electric motors, and implementing a patient weight monitoring system using load cells. Testing is conducted to validate the reliability of the new system in bed movement and patient weight measurement. The results indicate the successful conversion of beds into electric ones, with electric motors capable of lifting headrests up to a load of 150 kg. The patient weight monitoring system also proves accurate, with an average error of approximately 1.1% across a test load range of 10-150 kg. Additionally, the IoT communication system successfully stores and displays data in a database, accessible via an Android application. Thus, this development contributes positively to healthcare services by enhancing efficiency and accuracy in patient care. The implementation of electric motors and patient weight monitoring systems is expected to meet national healthcare standards and pave the way for further developments in smart bed patient implementation. Overall, this research underscores the importance of integrating technology to enhance the quality of healthcare services.